DAYA SAING USAHATANI KARET RAKYAT DI DESA KEMBANG TANJUNG KECAMATAN ABUNG SELATAN KABUPATEN LAMPUNG UTARA - Alghoziyah Alghoziyah; R Hanung Ismono; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purposes of this research are to find out the financial viability of smallholder rubber farming in Kembang Tanjung Village and the competitiveness of smallholder rubber farming in Kembang Tanjung village. This research was conducted in Kembang Tanjung, Subdistrict of South Abung, North Lampung regency. The numbers of samples in this study were 63 people obtained by proportional random sampling. The analytical methods used to answer the goals were financial analysis method and Policy Analysis Matrix (PAM).  The results obtained from this research showed that smallholder rubber farming in Kembang Tanjung are profitable and feasible.  The smallholder rubber farming at Kembang Tanjung has competitiveness (competitive and comparative advantage), it could be seen by the PCR value as 0,17 (<1) and the DRC amounted to 0,09 (<1).  The indicator means that the commodity of smallholder rubber farming at Kembang Tanjung village emerging government policies in term of improving production effeciency which was the policy in subsidizing fertilizers for farmers.Key words: competitiveness, financial feasibility, PAM, rubber